2022
DOI: 10.1155/2022/4632501
|View full text |Cite
|
Sign up to set email alerts
|

Left Nonrecurrent Laryngeal Nerve: A Very Unusual Finding during Thyroid Surgery

Abstract: Background. Identifying the inferior laryngeal nerve is one of the main concerns in thyroid surgery. The typical recurrent position occurs due the relative position between the vagus nerve and the larynx during the last 3 branchial arches development. In rare cases, this nerve does not loop under the right subclavian artery or the aortic arch. This abnormality is present in 0.7% of patients and is associated with the presence of anatomical vascular anomalies. The left non-recurrent inferior laryngeal nerve is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Furthermore, two studies reported that it is important to consider the possible variants of the RLN or the NLRN based on a timely physical and imaging examination, which could reduce iatrogenic damage such as injury to the ITA, structures that run through the tracheoesophageal groove, or by last structures associated with innervation of the RLN [ 11 , 58 ]. One study reported that clinical and preoperative evaluation is important because the presence of NRLN is associated in some cases with dysphagia and silhouette abnormalities visible on radiographs in the mediastinal region, thus avoiding surgical complications [ 59 ]. One study reported preoperative paralysis of the vocal cords due to the compression of a variant of the RLN route associated with a thyroid tumor [ 60 ].…”
Section: Clinical Considerationmentioning
confidence: 99%
“…Furthermore, two studies reported that it is important to consider the possible variants of the RLN or the NLRN based on a timely physical and imaging examination, which could reduce iatrogenic damage such as injury to the ITA, structures that run through the tracheoesophageal groove, or by last structures associated with innervation of the RLN [ 11 , 58 ]. One study reported that clinical and preoperative evaluation is important because the presence of NRLN is associated in some cases with dysphagia and silhouette abnormalities visible on radiographs in the mediastinal region, thus avoiding surgical complications [ 59 ]. One study reported preoperative paralysis of the vocal cords due to the compression of a variant of the RLN route associated with a thyroid tumor [ 60 ].…”
Section: Clinical Considerationmentioning
confidence: 99%
“…При этом, по данным метаанализа, такой тип нерва среди всех выявленных НВГН отмечен в 2,9% случаев [16]. Кроме того, авторами описано 4 левосторонних варианта нерва без транспозиции органов в сочетании с правой дугой аорты и левой аберрантной подключичной артерией [17][18][19][20].…”
Section: обоснованиеunclassified